Antioxidant, Anti-Inflammatory, Acute Oral Toxicity, and Qualitative Phytochemistry of The Aqueous Root Extract of (Hochst. Ex Oliv. & Hiern.) - Evans Kapanat Akimat; George Isanda Omwenga; Gervason Apiri Moriasi; Mathew Piero Ngugi (SAGE Publishing, 2021)
The root and leaf extracts of Launaea cornuta have been locally used in traditional medicine for decades to manage inflammatory conditions and other oxidative-stress-related syndromes; however, their pharmacologic efficacy has not been scientifically investigated and validated. Accordingly, we investigated the in vitro antioxidant activity, anti-inflammatory ( in vitro, ex vivo, and in vivo ) efficacy, acute oral toxicity, and qualitative phytochemical composition of the aqueous root extract of L. cornuta . The ferric-reducing antioxidant power (FRAP) and the 2,2-diphenyl-2-pycrylhydrazyl (DPPH) radical scavenging test methods were used to determine the studied plant extract's antioxidant activity. Besides, the anti-inflammatory efficacy of the studied plant extract was investigated using in vitro (anti-proteinase and protein denaturation), ex vivo (membrane stabilization), and in vivo (carrageenan-induced paw oedema in Swiss albino mice) methods. The studied plant extract demonstrated significant in vitro antioxidant effects, which were evidenced by higher DPPH radical scavenging and FRAP activities, in a concentration-dependent manner ( p  < 0.05). Generally, the studied plant extract exhibited significant in vitro, ex vivo, and in vivo anti-inflammatory efficacy, respectively, and in a concentration/dose-dependent manner compared with respective controls ( p  < 0.05). Moreover, the studied plant extract did not cause any observable signs of acute oral toxicity, even at the cut-off dose of 2000 mg/Kg BW (LD 50  > 2000 mg/Kg BW), and was thus considered safe. Additionally, qualitative phytochemistry revealed the presence of various antioxidant- and anti-inflammatory-associated phytochemicals, which were deemed responsible for the reported pharmacologic efficacy. Further studies to characterise bioactive molecules and their mode(s) of pharmacologic efficacy are encouraged.